Promising Therapeutic Strategies Against Microbial Biofilm Challenges - Zhang, Kaiyu; Li, Xin; Yu, Chen; Wang, Yang (Frontiers in Cellular and Infection Microbiology, 2020)
Biofilms are communities of microorganisms that are attached to a biological or abiotic surface and are surrounded by a self-produced extracellular matrix. Cells within a biofilm have intrinsic characteristics that are different from those of planktonic cells. Biofilm resistance to antimicrobial agents has drawn increasing attention. It is well known that medical device- and tissue-associated biofilms may be the leading source for the failure of antibiotic treatments and can cause many chronic infections. The eradication of biofilms is very challenging. To overcome biofilm-related infections, many researchers are working in this field, and some novel strategies have been developed and identified as being effective and promising. Nevertheless, more preclinical studies and well-designed multicenter clinical trials are critically needed to evaluate their prospects. Here, we review information about the mechanisms of biofilm drug resistance and recent progress of alternative therapies and promising strategies against microbial biofilms. We also summarize the strengths and weaknesses of these strategies in detail.